Parents’ perceptions and expectations of COVID-19 vaccination for children in Banda Aceh - Teuku Ade Prasetia; Bakhtiar Bakhtiar; Heru Noviat Herdata; Nora Sovira; Anidar Anidar; Eka Yunita Amna; Syafruddin Haris (Paediatrica Indonesiana, 2023)
Background Parents usually make the decisions on COVID-19 vaccinations for their children under the age of 18. Objective To explore parents' perceptions and expectations of COVID-19 vaccination for children in Banda Aceh. Methods This study used a qualitative design with a phenomenological approach. Data were collected through in-depth interviews of 36 parents in Banda Aceh. The data were analyzed qualitatively through thematic analysis. Results Three themes were studied: (1) perceptions of parents willing to have their children vaccinated against COVID-19, (2) perceptions of parents who refused or delayed their children’s vaccination against COVID-19, and (3) parents' expectations regarding COVID-19 vaccination in children. Benefits of the vaccine and government policy were among the reasons that parents were willing to have their children vaccinated. Vaccine safety concerns, lack of information, strong immunity, healthy lifestyle, and religious beliefs were the main reasons for parental refusal or delay in vaccinating their children. Reduced cases of COVID-19 and the end of the pandemic, not being infected, developing immunity, and no adverse events following immunization, face-to-face learning in schools, as well as increased education and socialization from the government, society that was critical and selective in receiving information were the expectation of parents regarding COVID-19 vaccination in children. Conclusion The perception of vaccine benefits and government policy influence parents to have their children vaccinated, while perception of vaccine safety concerns, lack of information, strong immunity, healthy lifestyle, and religious beliefs influence parents to refuse or delay their children being vaccinated. Parents' expectations regarding COVID-19 illness, their children’s response to the vaccine and education, as well as the government’s and society’s roles during the pandemic are qualitatively elucidated.